Ordenamento fundiário na várzea de Santarém e seus impactos socioambientais - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The conceptual understanding of the “várzea” (floodplains) and its multiple uses is something that brings an eminent demand. In fact, such spaces need regularization by the government in favor of the riverine populations that occupy them historically. The experience of regularization of 45 lowland areas in the Lower Amazon, in the form of an agroextrativist Settlement Project, was a significant advance. The emission of Real Use Right Concession Contracts (CDRU) or of Assignment Contracts (CCU), in the individual or collective modality, thus, comes to the rescue of families who seek to recognize their possessions in order to have access effectiveness of public policies. The paper aims to know if these documents can enhance the social and environmental sustainability of this environment, especially the natural fields and lakes, which suffer from predatory fishing. In order to answer this question, some points were considered, such as: a) analysis of the normative instruments used in relation to these areas (to understand which instruments to guide the use of the territory will be possible for the planning and thus to consider their socioenvironmental impacts on norms of use already existing in the communities); b) identification of the actors responsible for the planning policy of that territory and the role of each one; c) understanding the profile of the occupants and occupation history in order to know if the land regularization models respect the traditional way of life of the riverside inhabitants; d) understanding the planning strategy in areas already in the process of regulation, the study presents contributions and suggestions to the managers and riverside. The methodology of this research can be understood in the field of critical observation, performing several stages among them the bibliographical and documentary research; conducting interviews with local actors and field trips in order to better understand the existing social dynamics and the forms of territorial organization of the communities adopted by them over the years. The main conclusion of the study, among others, was that popular participation in the management of natural resources is fundamental for the success of the model of regularization and social development of these traditional populations, with respect to the citizenship of the same and the future generations of riverside.
Keywords: Várzea; Regularização Fundiária; Baixo Amazonas; População Tradicional; Posse; Legislação; DIREITOS HUMANOS, SOCIEDADE E CIDADANIA AMBIENTAL; CIÊNCIAS DA SOCIEDADE